RNA sensor response in HeLa cells for transfected mRNAs prepared in vitro by SP6 and HiT7 RNA polymerases: A comparative study - Nagaraj, Siranjeevi; Stankiewicz-Drogon, Anna; Darzynkiewicz, Edward; Grzela, Renata (Frontiers in Bioengineering and Biotechnology, 2022)
In vitro transcribed (IVT) synthetic mRNAs are in high demand due to their attractive bench to clinic translational processes. Mainly, the procedure to make IVT mRNA using bacteriophage RNA polymerases (RNAP) is relatively uncomplicated and scalable to produce large quantities in a short time period. However, IVT mRNA preparations are accompanied by contaminants such as double-stranded RNA (dsRNA) as by-products that elicit undesired cellular immune responses upon transfections. Therefore, removing dsRNA contaminants is critical in IVT mRNA preparations for therapeutic applications. One such method to minimize dsRNA contaminants is to use genetically modified thermostable bacteriophage polymerase, HiT7 RNAP that performs IVT reaction at a higher temperature than typically used. However, the cellular RNA sensor response for IVT mRNA preparations by HiT7 RNAP is not characterized. Here, we compared the cellular RNA sensor response for mRNAs prepared by HiT7 RNAP (at 50 C) and SP6 RNAP (at 37 C) in HeLa cells. We show that IVT mRNA preparations by HiT7 RNAP reduced the dsRNA levels and dsRNA specific RNA sensor response (retinoic acid-inducible gene I, RIG-I and melanoma differentiation-associated 5, MDA5) compared to the IVT mRNA preparations by SP6 RNAP. Similarly, the incorporation of pseudouridine nucleotides instead of uridine nucleotides reduced dsRNA sensor response and increased the mRNA translation. Overall, the least dsRNA mediated RNA sensor response is observed when mRNA is synthesized by HiT7 RNAP and incorporated with pseudouridine nucleotides.